A rate-based transcutaneous CO2 sensor for noninvasive respiration monitoring. (2nd April 2015) - Chatterjee, M; Ge, X; Kostov, Y; Luu, P; Tolosa, L; Woo, H; Viscardi, R; Falk, S; Potts, R; Rao, G
Abstract: The pain and risk of infection associated with invasive blood sampling for blood gas measurements necessitate the search for reliable noninvasive techniques. In this work we developed a novel rate-based noninvasive method for a safe and fast assessment of respiratory status. A small sampler was built to collect the gases diffusing out of the skin. It was connected to a CO2 sensor through gas-impermeable tubing. During a measurement, the CO2 initially present in the sampler was first removed by purging it with nitrogen. The gases in the system were then recirculated between the sampler and the CO2 sensor, and the CO2 diffusion rate into the sampler was measured. Because the measurement is based on the initial transcutaneous diffusion rate, reaching mass transfer equilibrium and heating the skin is no longer required, thus, making it much faster and safer than traditional method. A series of designed experiments were performed to analyze the effect of the measurement parameters such as sampler size, measurement location, subject positions, and movement. After the factor analysis tests, the prototype was sent to a level IV NICU for clinical trial. The results show that the measured initial rate of increase in CO2 partial pressure is linearly correlated with the corresponding arterial blood gas measurements. The new approach can be used as a trending tool, making frequent blood sampling unnecessary for respiratory status monitoring.